2003
DOI: 10.1021/jp026742r
|View full text |Cite
|
Sign up to set email alerts
|

Elastic Polarizable Environment Cluster Embedding Approach for Covalent Oxides and Zeolites Based on a Density Functional Method

Abstract: We present a new quantum mechanics/molecular mechanics (QM/MM) embedding approach for systems with directional polar covalent bonds. This “covalent elastic polarizable environment” (covEPE) scheme features a variational treatment of an energy expression that includes all degrees of freedom of both the QM region (the “cluster”) and the MM regions (the “environment”). The method completely and explicitly includes both the electrostatic and mechanical interactions between a QM model cluster and its environment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 63 publications
3
119
0
Order By: Relevance
“…The model studies with covEPE method suggested that the DE energies of the acid sites decrease by about 20-25 kJ/mol along the series faujasite>CHA>HZSM-5. 19,20 This observation is in agreement with experimental trend in the acidity of these zeolites tentatively estimated from measured shifts of the OH frequency upon adsorption of a probe CO molecule. 51 The presence of additional metal cation in vicinity to the bridging OH groups has substantial influence on the Brnsted acidity.…”
Section: Bridging Hydroxyl Groupssupporting
confidence: 88%
See 1 more Smart Citation
“…The model studies with covEPE method suggested that the DE energies of the acid sites decrease by about 20-25 kJ/mol along the series faujasite>CHA>HZSM-5. 19,20 This observation is in agreement with experimental trend in the acidity of these zeolites tentatively estimated from measured shifts of the OH frequency upon adsorption of a probe CO molecule. 51 The presence of additional metal cation in vicinity to the bridging OH groups has substantial influence on the Brnsted acidity.…”
Section: Bridging Hydroxyl Groupssupporting
confidence: 88%
“…Three different hybrid QM/MM methods based on summation scheme have been developed in the last years for zeolites and similar systems: method included in ChemShell software, 32,33 the scheme developed by Sulimov et al 18 , and covEPE method. [19][20][21] A hybrid MP2/DFT method was proposed by Tuma and Sauer 22 for theoretical simulation of problems that involve both bond rearrangements and van-der-Waals interactions. This method combines second-order Mller-Plesset perturbation theory (MP2) as high-level method for the reaction site with DFT as low-level method for the large part of the zeolite system under periodic boundary conditions.…”
Section: Computational Modelling Of Nanoporous Materialsmentioning
confidence: 99%
“…18 The relative stability of the acidic protons is in agreement with other cluster calculations using 13T atoms 41 and an embedded 5T cluster. 42 In periodic calculations 20,37,39,41 the H 1 proton position becomes more stable. As can be seen from Table I the proton affinities of the oxygen atoms show a strong dependence on the choice of the cluster.…”
Section: A Zeolite Cluster Without Adsorbatementioning
confidence: 99%
“…Compared to our results, the difference in the proton affinity of the two oxygen atoms is larger, 17 kJ/mol, and in their calculations the oxygen atom O 1 has a higher proton affinity than the oxygen atom O 3 . Using a different embedding method Naslusov et al 42 have found the proton affinity of the O 3 oxygen atom to be higher by 6 kJ/mol than that of the O 1 oxygen atom. 26,39 and embedded 2T clusters.…”
Section: A Zeolite Cluster Without Adsorbatementioning
confidence: 99%
“…[10,11] These methods allow one to describe accurately adsorption on metal-oxide surfaces of varying degrees of covalence while taking relaxation effects into account. We employed EPE embedding for ionic oxides to elucidate the adsorption of isolated Pd atoms on regular sites and oxygen vacancies of MgOA C H T U N G T R E N N U N G (001).…”
Section: Introductionmentioning
confidence: 99%